«Рalazzo еn fortezza» на Гончарівці в Батурині - Бондар, О. (Сiверянський лiтопис, 2018)
Стаття присвячена реконструкції топографічної структури унікального оборонно-архітектурного комплексу – резиденції гетьмана Івана Мазепи в Батурині
на Гончарівці. На основі зображальних, археологічних та писемних джерел вдалося
створити графічний варіант реконструкції планувальної системи садиби, остаточно
спростувати припущення про декоративність її оборонних споруд. Навпаки, вдалося
довести те, що фортифікації садиби виконані з використанням тогочасних новітніх
європейських досягнень оборонно-інженерної справи. Також наведено основні аналогії
подібних садиб на території тогочасної Гетьманщини. The article is devoted to the reconstruction of the topographical structure of the unique
defensive and architectural complex of the residence of Hetman Ivan Mazepa in Baturin
in the Goncharivka. Unfortunately, this complex has not survived to our days in its original
form. Ground structures were destroyed in the second half of the 18th century, and the
fortress itself suffered in the 20th century. Due to the works of the Baturin’s Ukrainian and
Canadian archeological expedition from 1995 to 2017, today we have important results for
the reconstruction and understanding of the development of this architectural complex.
This complex was founded around the 1690’s. It was situated 2 km from the fortress
Baturin. The palace, the wooden church, ancillary farms were on the territory of the manor
and altogether made a unique architectural ensemble. A graphic reconstruction of the manor
design Goncharivka was made on the basis of pictures, archaeological and written sources.
The basis of this reconstruction was laid in the plan of the Goncharivka 1862. This plan was
combined with modern topographic survey and archaeological data. This work has yielded
very interesting results.
The article suggested that Ivan Mazepa’s homestead on Goncharivka was the first manor
house with a regular layout on the territory of the Left Bank of Ukraine in the late 17th – early
18th centuries.
Finally, the myth about the decorative constructions of the manor’s fortifications is
debunked. It has been proven that the fortification works on Goncharivka were made using
the new European achievements in the fortification case. Fortification elements of the manor
were planned in the Dutch system of earthworks: a straight earth walls, bastions in the form
of barbets, entry between the bastions and polygonal planning. The defense system of the
manor relied on the cross fire of artillery. The article also shows the main analogues of similar
manors on the Hetmanat territory.